(untitled) (Comprehensive Journal of Science, 2026)
Ecotourism is one of the patterns and methods through which the state seeks to achieve economic benefits and exploit them by future generations. Exploring natural and human resources, And paying attention to sustainable tourism development programs within a general framework for development in the country, so that part of it contributes to solving the general problem of developing coastal and desert areas in the region, taking into account the capabilities available to society and its specificity, within the framework of bridging the large gap between traditional development and ecotourism that is available on sound scientific bases and well planned planning. It takes into account the privacy of all parts of the region, while standing on the most important challenges and obstacles and proposing some recommendations that would activate the role played by comprehensive tourism development in order to achieve the desired tourism goals.